Development and inter-rater reliability of a tool assessing hypnotic communication behaviours adopted by nurses caring for children with cancer: The Sainte-Justine Hypnotic Communication Assessment Scale. (April 2018) - Aramideh, Jennifer; Mizrahi, Terry; Charest, Marie-Claude; Plante, Caroline; Duval, Michel; Sultan, Serge
Highlights: The objective is to develop a scale to code for professionals' behaviours when they are using hypnotic communication to deal with pediatric pain. We used an iterative process to assess clarity and understandability of items on a subset of video encounters. The final version of the scale comprises 11 items dealing with rapport and technical skills. The inter-rater reliability of the scale was excellent. The results support future systematic analysis of the validity of the scale and is encouraging as for its use to measure communication behaviours following training. Abstract: Background: Several studies in pediatric oncology have shown the successful effects of using hypnotic communication techniques (HCTech) during painful medical procedures. Since no studies assessed the precise use of these techniques with a validated tool, it is unsure that the observed relationships involve the use of HCTech. Objectives: To develop a scale evaluating healthcare professionals' behaviours when using HCTech and to evaluate its inter-rater reliability. Methods: This study involved the preliminary steps of the Sainte-Justine Hypnotic Communication Assessment Scale (SJ-HCAS) development process. As part of a larger intervention study, the SJ-HCAS was developed in three steps by five experts and four lay raters using an iterative process applied to subsets of video-recorded nurse-patient interactions. The development aimed to maximize clarity and precision of items as well as minimize redundancy amongst items. Inter-rater reliability was assessed in a randomly selected sample of 1/3 of collected video-recorded interactions (n = 42). Results: The final version of the scale is composed of 11 items categorized in two domains pertaining to Relationship and Technique. We found excellent inter-rater reliability for both subscores and total score in two independent inter-rater comparisons (median ICC = 0.879), with most items showing very good to perfect inter-rater reliability (median Kappa = 0.847). Conclusions: The results support further work with the SJ-HCAS. The scale has the potential to help ensure the integrity of hypnotic communication training in children which could ultimately promote the dissemination of the practice of HCTech.